In Silico Identification of MicroRNAs with B/CYDV Gene Silencing Potential - Maryem Bouallègue; Dhia Bouktila; Maha Mezghani-Khemakhem; Pierre Capy; Mohamed Makni (Brazilian Archives of Biology and Technology)
ABSTRACT Computational investigation of a set of publicly available plant microRNAs revealed 19 barley- and other plants-encoded miRNAs and their near-complement reverse sequences (miRNA*) that have potential to bind all B/CYDV open reading frames (ORFs) except ORF0 and ORF6. These miRNAs/miRNAs*, their binding positions and targets are discussed in the context of biological protection of cereals against B/CYDV, based on antiviral silencing.